AN ANALYSIS OF 8 FORMULAS FOR FORMING ALIFIA HIDAYATI’S SOCIAL BRANDING ON THE TIKTOK ACCOUNT @RUMROIJEN - Edi Nurwahyu Julianto; Ayang Fitriyanti; Yoma Bagus Pamungkas (Journal of Innovation Research and Knowledge, 2024)
One communication strategy that instills a positive perception of a person in the public is carrying out personal branding. The presence of TikTok has the function of being able to create a digital marketing strategy and build a brand, with TikTok being able to influence the behavior of its followers. One of them is the TikTok celebrity Alifia Hidayanti or known as Mbak Yu, who is famous because she likes to wear kebaya to travel around Semarang and other areas to visit unique places. This research uses a qualitative method with a descriptive approach, focusing on a research case study, namely finding out Mbak Yu Berkebaya's personal branding through her Tiktok social media account @rumroijen. With his unique appearance, he is different from young people his age, making him entertaining and attractive for introducing Javanese culture to his followers. Mbak Yu Berkebaya has consistently built personal branding using 8 formation concepts, namely The Law of Specialization, The Law of Leadership, The Law of Personality, The Law of Distinctiveness, The Law of Visibility, The Law of Unity, The Law of Persistence, and The Law of Goodwill, on his Tiktok account, makes him better known and increases his personal value and selling power. So he has had many opportunities to collaborate with various events, brands and companies